The Popularity of the Regent Figures and Slogans in the Perspective of Socio-Cultural Mediatization - Yudha, Reza Praditya (ARISTO, 2023)
The purpose of this study is to find out the popularity of the figures and slogans of the Tulungagung regents. This study elaborates previous researches stating that figures and slogans are forms of messages in the peripheral route that influence the people's political attitudes. This study argues that the communal culture of the people corresponds to the processing of information through the peripheral route. This study uses a mixed method that quantitatively surveys 192 respondents to find out the popularity of the regent figures and slogans in the last 23 years, as well as qualitatively applies the concept of mediatization to understand the socio-cultural context underlying the way people interpret the figure and the slogan of the regent. This study finds that the people have experienced a peaceful and harmonious social situation during the reign of Heru Tjahjono who coined the slogan "guyub rukun". The people are trying to raise the spirit of togetherness and harmony by reconstructing the slogan of "guyub rukun" in various sites and activities. This makes Heru Tjahjono and â€œguyub rukunâ€ popular in the people's daily lives.